(untitled) (Research Announcements "Heritage BG", 2025)
Mass wellness practices are different forms of physical activity aimed at large groups of people with a holistic impact. Fitball classes build the skills and habits of practitioners to effectively use exercise and sport in their everyday lives. Recreational wellness programs are effective practices with high social and educational impact. Mass education in the school sports system has its value related to proper physical development and health enhancement of the "golden fund of the nation - children" with a chance for a dignified and fulfilling life. Physical skills are of great educational value, with the fitball program providing tremendous functional benefits to the general health status of its practitioners. This paper establishes the attitudes and activity levels of students in Fitball groups. References: Nesheva 2009: Nesheva Irina. Fitbolat kato fitnes distsiplina i predizvikatelstvo za detsata. Sb. „Optimizatsia i inovatsii v uchebno-trenirovachnia protses. Uni izd. „Sv. Kl. Ohridski “. Nauchna konferentsia posvetena na 80 godini sport v Alma Mater – Departament po sport. Sofia, 153-156. ISBN: 978-954-07-2987-9 Badau et al. 2021: Badau Dana, Adela Badau, Gabriel Manolache, Mircea Ion Ene, Adriana Neofit, Vlad Teodor Grosu, Virgil Tudor, Radu Sasu , Raluca Moraru, and Liviu Moraru. The Motor Impact of the Static Balance in the Up Plank Position on Three Different Balls in Physical Activities of Physical Education Students. Int. J. Environ. Res. Public Health 18(4), 2043, Available at: https://doi.org/10.3390/ijerph18042043 (1.07.2024) Brent 2016: Brent Little. Effectiveness of Swiss ball core-exercises versus stable surface core-exercises on perceived disability in adults with chronic low back pain. Health and Medical Sciences – Occupational therapy. PhD Dissertation, Degree Level – Doctoral, College Health and Human Services, Department Physical Therapy, 2016-10-14T23:45:30Z. Available at: http://hdl.handle.net/10211.3/179720 (1.07.2024) Das, Kumar, Dutta 2016: Das Subhanjan, Kumar C K Senthil, Dutta Abhijit. A comparitive study to know the effectiveness of prone back extension exrecises and swiss ball exercises on back extensor muscles performance. IJPHY, 2016-08-01T00:00:00Z. International Journal of Physiotherapy, Vol 3, Iss 4. Available at: DOI: https://doi.org/10.15621/ijphy/2016/v3i4/111052 Dimitrova, 2019: Dimitrova Bistra. Quality assessment about standards for wellness services and certified skills of specialized staff. DOI: 10.15547 / tjs.2019.02.007. Trakia Journal of Sciences, Vol. 17, No 2, 143-149, ISSN: 1313-3551 (online). Available at: http://tru.uni-sz.bg/tsj/Vol.17,%20Suppl.2,%202019/7.pdf (20.06.2024) Ivanova et al. 2016: Ivanova, Elena, Bogomilova, Stanislava, Nikolova, Donka. Advantages and opportunities of Fitball for prevention and treatment in kinesitherapy. Proceedings from the scientific conference Sliven 2016 contemporary trends in nursing and midwifery; 166-169; Varna Medical Forum; Vol 5, Suppl 3. Available at: DOI: http://dx.doi.org/10.14748/vmf.v5i0.1996 Lehman, Hoda, Oliver 2005: Lehman Gregory, Hoda Wajid, Oliver Steven. Trunk muscle activity during bridging exercises on and off a Swissball. Springer Science and Business Media LLC. Journal-article Chiropractic & Osteopathy, Vol 13, Iss 1, ISSN 1746-1340. Available at: https://doi.org/10.1186/1746-1340-13-14.